PENGARUH FAKTOR INTERNAL DAN FAKTOR INTERNAL TERHADAP KEPUTUSAN PEMBELIAN DI MINIMARKET LIMA-LIMA BENOWO SURABAYA - ATUL MAHMUDAH, RIFA (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
The Consumers need to the type of product and services are constantly changing. They fill their need with shopping at a Minimart. The Consumers are influenced by internal and external factors in the purchase decision. Sometimes they are influenced by internal factors only , or external factors only and some consumers also argue that they shop in Stores due to other factors. The type of this research is a survey research with quantitative approach. By taking the population of 120 consumers who was shopped in August with a sample of 98 consumer. With the analysis of multiple linear regression test with SPSS for windows version 16. (1) the condition of internal factors and external factors consumers who shop at the minimarket Lima-lima Benowo Surabaya in relationship strong. It is supported by the results of research that shows that the position of the Internal factors is 64.4% and the position of the external factors is 89,4% (2) Internal factors and external factors influence consumer purchase decisions significantly to either simultaneously or partial Keywords: Internal factors, External factors, Purchase decisions